Paleoenvironmental and biostratigraphic constraints for uppermost cretaceous (Maastrichtian) sedimentary successions of northern South America - Patarroyo Camargo, German David (Universidade do Vale do Rio dos Sinos, 2024)
One of the major environmental and biotic turnovers of the Phanerozoic occurred at the Cretaceous- Paleogene (K-Pg) transition, being the focus of countless scientific studies that addressed the timing, mechanisms and consequences of this global event. Though less explored, Late Cretaceous oceanic settings also underwent significant paleoenvironmental changes, due to a combination of global or regional paleoceanographic and tectonic events. This study aims to reconstruct paleoenvironmental conditions on a series of Maastrichtian localities along the equatorial South American margin. To have a better understanding of low-latitude water masses during that time, we applied high-resolution micropaleontological (foraminifers) and geochemical (sediment elemental ratios, carbon isotopes, among others) methods in shallow marine units from northern Colombia, and in deep-sea sites from the tropical Atlantic Ocean. Two Maastrichtian localities were considered in Colombia: (1) Core Diablito-1E (Colón Formation, Cesar-Ranchería Basin), and (2) the Aguablanca Creek section (Umir Formation, Middle Magdalena Valley). In general, foraminiferal assemblages were dominated by benthic taxa (Maastrichtian regional biozones Siphogenerinoides bramletti to Ammobaculites colombiana), and planktonic foraminiferal assemblages were mostly composed of Guembelitria cretacea and heterohelicids. Ostracods and calcareous nannofossil were also studied to provide integrated paleoenvironmental interpretations. Despite their potential, both microfossil groups had been poorly studied in this region. Integrated microfossil assemblages and sediment elemental ratios (Zr/Rb, Fe/Ca, V/Cr and Sr/Ba) in both localities clearly indicated a transition from inner platform settings, with moderately oxygenated bottom waters, to sublittoral conditions. Throughout the studied sections, weathering intensity increased, accompanied by increased input of terrigenous sediments. These environmental disturbances were related to the geological evolution of extensive epicontinental seas that occupied northern South America, and gradually disappeared due to sea level fluctuations, and the onset of the Andean orogeny since the Maastrichtian. To track paleoenvironmental disturbancesin the deep-sea, two Maastrichtian localities were surveyed in the tropical Atlantic Ocean: (1) Ocean Drilling Program (ODP) Hole 1258A (Demerara Rise), and (2) ODP Hole 1001B (Nicaraguan Rise). At Hole 1258A, high-resolution geochemical and benthic foraminiferal analyses suggest the occurrence of paleoenvironmental shifts during the entire Maastrichtian, related to changes in the intermediate to deep-water oxygenation and surface productivity, as well as a sudden dissolution episode in the earliest Maastrichtian. For instance, selected taxa (Aragonia, Nuttallides truempyi, Coryphostoma, Strictoscomella, among others), and the distribution of redox-sensitive trace metals (Ni, Cu) along the core, indicated suboxic bottom water conditions, with oxygenation pulses during the mid-Maastrichtian event (MME), which was identified by a high-resolution stable carbon isotope (δ 13C) record at the site. Moreover, sediment elemental ratios (log(Fe/Ca), Si/Ti, Fe/K) indicated fluctuations of biogenic silica and carbonate export via surface productivity, and probable disturbances of the regional hydroclimate since the early Maastrichtian. These disturbances of local surface productivity and bottom water oxygenation on Demerara Rise were likely related to the MME and the onset of the late Maastrichtian warming event, both linked to a higher interference of high-latitude deep-waters on the tropics and likely latitudinal migrations of the Paleo-Intertropical Convergence Zone (PITCZ). On the other hand, tracking paleoenvironmental disturbances at Hole 1001B was more challenging since diagenetic issues hampered good microfossils preservation, whose assemblages suggested a typical bathyal setting. However, the sedimentary archive of Hole 1001B was sensitive enough to allow identifying of the K-Pg boundary with a preliminary δ13C survey, also indicating subtle changes of surface paleoproductivity and bottom water conditions during the late Maastrichtian, as suggested by sediment elemental ratios (log(Fe/Ca), Si/Al, Ba/Al, Fe/K) and concentrations of redox-sensitive trace metals (Ni, Zn, V) along the core. Finally, the analysis of mercury (Hg) concentrations as a proxy for widespread volcanic activity was conducted in three of the studied localities: Sites Diablito-1E, ODP Holes 1258A and 100B. Considering the shallowing processes underwent by core Diablito-1E, and the poorly explored influence of the northern South American volcanism during Maastrichtian, Hg concentrations could not be exclusively linked to a single volcanic source (Deccan or regional volcanism). Bulk sediments δ 13C analyses at Core Diablito-1E, the first ones conducted in Maastrichtian rocks from this area, indicate that the lowlatitude sedimentary record has the potential to track perturbations of the global carbon cycle. Moreover, the sedimentary records from Demerara Rise and Nicaraguan Rise illustrated significant Hg peaks along the Maastrichtian, which based on their proposed age models and comparisons with other Maastrichtian localities, would evidence the influence not only of Deccan volcanic episodes but also of the less studied volcanic pulses in the Caribbean during the late Maastrichtian. The role of those widespread processes on the low latitude climate is a promising field of study. These results clearly pointed out that the northern South America region was particularly sensitive to paleoenvironmental disturbances during the Maastrichtian, reflecting their highly complex geological evolution during the latest Cretaceous.
Keywords: Sedimentos; Geologia estratigráfica - Cretáceo; Paleontologia - Cretáceo; sediments; Stratigraphic geology - Cretaceous; Paleontology - Cretaceous; ACCNPQ::Ciências Exatas e da Terra::Geologia